Low frequency vibrations in disc brakes at high car speed. Part II: mathematical model and simulation. (4th August 2014) - Aviles, R.; Hennequet, G.; Amezua, E.; Vallejo, J.
In the present paper, a mathematical model is constructed for judder in disc brakes at high speed. Vehicle suspension is modelled by means of finite elements. Vibration modes and frequencies are derived that can be used in the classification of modes in main and secondary based in the relative disc–calliper displacement; the finite element model is also used as well as in forced–response analysis. Brake pads are defined through the friction coefficient as a function of speed, pressure, and temperature, in light of which one may consider the various braking conditions and types of pad. Since the line of reasoning introduces equivalent–damping terms into the equations of dynamics, these equations cannot be uncoupled by means of modal transformation. Two techniques are proposed for the solution of the problem. One of these consists in an examination of the 'main–modes', while the other is based on direct integration of the quasi–uncoupled equations. A computer program has been implemented which allows the simulation of this kind of judder with different pads, brake systems and braking conditions.